Effect of stool size and consistency on defecation. Issue 10 (October 1987) - Bannister, J J; Davison, P; Timms, J M; Gibbons, C; Read, N W
Abstract : The ability of subjects to expel from the rectum objects simulating stools of different characteristics was assessed in paired studies carried out in a total of 58 normal subjects and 25 young women with severe constipation. Our results showed that a lower percentage of normal subjects and a lower percentage of constipated patients were able to pass a 1.8 cm incompressible sphere compared with a 50 ml deformable balloon, although constipated patients found it more difficult than normal subjects to expel both types of simulated stool. It was also more difficult for normal subjects to pass a soft compressible silicon rubber simulated stool than a stool made up of a similar volume of incompressible 1 cm wooden spheres contained in a cylindrical latex envelope, but both objects were much easier to pass than the same number of 1 cm spheres placed loose within the rectum. When normal subjects were instructed to expel single incompressible spheres of different sizes placed in the rectal ampulla, the intrarectal pressure and the time needed to pass these objects varied inversely with their diameter. These results suggest that more effort is required to expel stools from the rectum if they are small and hard than if they are large and soft.